COMMUNICATION RISK OF STAKEHOLDERS IN PREVENTING FOREST AND LAND FIRES IN RIAU PROVINCE - Badri, Muhammad; Lubis, Djuara P; Susanto, Djoko; Suharjito, Didik (Jurnal Ilmiah Peuradeun, 2018)
Riau Province is one of the prone areas of forest and land fires in Indonesia. Fires in Riau have occurred since 1997 and peaked during the period of 2014 to 2015. Since that time, the government and other stakeholders had begun to change the paradigm of forest and land fire prevention, from preventing to handling. This study aims to analyze the communication process among stakeholders in preventing Karhutla (Forest and Land Fires) in Riau Province. The study was conducted by using qualitative methods through semi-structured interview toward 14 informants representing government communication roles, forestry and palm oil industries, researchers, NGOs, mass media, and The Fire Care Community (Masyarakat Peduli Api/MPA). The results of the study explain that all stakeholders have responses that fire intentionally caused by individuals and organized groups on open land, corporate land and community land. The planning and implementation of risk reduction are performed through various communication channels such as Karhutla Task Force, direct communication and media usage, especially WhatsApp, mass media and social media. In general, communication in expert modules is still dominated by government and minus researchers, while in public; the role of stakeholders is almost equal.